A Middle East free of weapons of mass destruction : a new approach to nonproliferation - Musavian, Hossein; Kiyaei, Emad (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"The establishment of a Middle East zone free of nuclear weapons, a concept more recently broadened to cover all weapons of mass destruction (WMD), has been before the international community for decades. In this book, two experts from the region explore why the matter remains unresolved, and outline a comprehensive yet achievable roadmap to a Middle East free of WMD. Weapons of mass destruction pose an existential threat to global peace and security. But nowhere is it more urgent to stem their spread than in the Middle East, a region fraught with mistrust and instability. Accounting for these geopolitical realities, including the ongoing talks to curb Iran's nuclear program, the authors present a practical and innovative roadmap to a Middle East free of weapons of mass destructions (WMD). They outline a phased approach toward disarmament in the region, prescribing confidence-building measures and verification tools to create trust among the region's governments. Their vision also sees the realization of a WMD-free zone within a broader regional agenda for security and cooperation to advance socioeconomic and political progress. This book will be of great interest to students and scholars of international relations, politics and security studies in the Middle East"--
Regionalization of the Iran Accord -- Multiple Initiatives to make the Zone a Reality -- A Phased Approach for the Zone -- WMD Challenges -- Broader Challenges -- Moving Forward.
OCLC-licensed vendor bibliographic record.
Keywords: Arms control -- Middle East; Weapons of mass destruction -- Government policy -- Middle East; Nuclear nonproliferation -- Middle East; Security, International -- Middle East; POLITICAL SCIENCE / General